The pleiomorphic actions of vitamin D and its importance for children - Se Young Kim (Annals of Pediatric Endocrinology & Metabolism, 2013)
Knowledge regarding the physiological role and dietary requirements of vitamin D has dramatically expanded over the past several decades. The "new" vitamin D is not only a mediator of calcium homeostasis, it also has important immunomodulatory, antimicrobial, and antiproliferative actions. In spite of the interest in vitamin D as a mediator in many chronic diseases of adulthood such as cancer and type II diabetes, less attention has been given to the implications of the new understanding of vitamin D for child and adolescent health. Recently, rickets caused by vitamin D deficiency is resurging in developed countries. Therefore, pharmacokinetic studies and epidemiologic research that incorporates clinical and functional outcomes are needed to clarify the role of vitamin D in growth and development in Korean children and adolescents and to determine vitamin D dietary requirements.